EFFECTIVENESS OF TUTORING SERVICES USING A HUMANISTIC APPROACH TO MULTISENSORY TECHNIQUES IN OVERCOMING READING LEARNING DIFFICULTIES (DYSLEXIA) IN CLASS VIII OF SMP HARAPAN 2 GENTENG: EFEKTIVITAS LAYANAN BIMBINGAN BELAJAR DENGAN PENDEKATAN HUMANISTIK TEKNIK MULTISENSORY DALAM MENGATASI KESULITAN BELAJAR MEMBACA (DISLEKSIA) DI KELAS VIII SMP HARAPAN 2 GENTENG - ella zuhairina firdaus; Siti Napisah; Ratna Wulandari (Program Studi Bimbingan dan Konseling, 2024)
This research was motivated by the existence of class VIII junior high school students who experienced reading disorders (dyslexia). The aim of this research is to determine the effectiveness of tutoring services using a humanistic approach to multisensory techniques to overcome difficulties in learning to read (dyslexia) in class VIII SMP Harapan 2 Genteng. This type of research is qualitative. Data collection techniques used include tests (pre-test, treatment, post-test), observation, interviews and documentation. The results of this study show that the pre-test results of students who had difficulty learning to read before being given treatment with multisensory techniques were very low. Students are not yet able to differentiate between several letters that are almost the same and students are not able to read letters that end in consonants (patents). However, after being given treatment with multisensory techniques assisted by reading card learning media, reading wheels and writing sand. Students experience many changes starting from being able to differentiate letters that are almost the same to reading words that end in consonants (patens).